2015
DOI: 10.1103/physrevlett.114.243003
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg Electrons in a Bose-Einstein Condensate

Abstract: We investigate a hybrid system composed of ultracold Rydberg atoms immersed in an atomic Bose-Einstein condensate (BEC). The coupling between the Rydberg electrons and BEC atoms leads to the excitation of phonons, the exchange of which induces Yukawa interaction between Rydberg atoms. Due to the small electron mass, the effective charge associated with this quasiparticle-mediated interaction can be large, while its range is equal to the healing length of the BEC, which can be tuned by adjusting the scattering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Ions immersed in a Bose-Einstein condensate were proposed as a medium for exploring the physics of mesoscopic particles [14], polarons [15], and electronphonon coupling [16,17]. Hybrid atom-ions systems are also discussed as possible implementations of quantum gates [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ions immersed in a Bose-Einstein condensate were proposed as a medium for exploring the physics of mesoscopic particles [14], polarons [15], and electronphonon coupling [16,17]. Hybrid atom-ions systems are also discussed as possible implementations of quantum gates [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the perturbing neutral atom wavefunction in the shape resonance potential is a new aspect to utilizing Rydberg excitations in dense, cold media. These dynamics must be considered for future proposals relying on utilizing a Rydberg atom in a BEC [33][34][35]. We have shown that the line broadening of the Rydberg levels in an ultracold and dense media is a direct manifestation of the underlying Rydberg-perturber PECs, by accounting only for elastic e --Rb(5S) scattering.…”
mentioning
confidence: 99%
“…Generalized versions of (7) include energy dependent scattering lengths, p-wave contributions as well as inhomogenous densities and have been employed successfully to describe the spectral response of single Rydberg impurities immersed in a dense BEC [87]. An intriguing application of Rydberg impurities in ultracold atomic gases is the production of textbook-like images of atomic orbitals by imprinting the shape of the Rydberg orbital onto the BEC density, which has been proposed theoretically in [75,76]. Another application is the creation of ionic impurities in BECs, which can be excited in the limit of large principal quantum numbers, typically n ∼ 160, when the Rydberg orbit exceeds the size of the atomic cloud [22].…”
Section: Polyatomic Ulrmsmentioning
confidence: 99%